2023
DOI: 10.3390/plants12091829
|View full text |Cite
|
Sign up to set email alerts
|

Soil Amendments and Foliar Melatonin Reduced Pb Uptake, and Oxidative Stress, and Improved Spinach Quality in Pb-Contaminated Soil

Abstract: Amending Pb-affected soil with biochar (BH) and magnesium potassium phosphate cement (MKC) reduces Pb uptake in plants. Moreover, foliar applications of melatonin and proline are also known to reduce plant oxidative stress and Pb uptake. However, little is known about combining both techniques, i.e., adding a combo immobilizing dose (CIA = mixture of BH and MKC at 50:50 ratio) in Pb-polluted soil and foliar application of proline and melatonin for reducing Pb uptake and oxidative stress in spinach. Control, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…One reason for this is due to the high cation-exchange capacity of arcillite that allows for the adsorption of positively charged ions due to negatively charged surfaces. We expected that arcillite as a substrate with high cation-exchange capacity would act like biochar, which holds a lower cation-exchange capacity, in its ability to diminish the uptake of toxic metals in plants by immobilizing the metal across the surface of the substrate via ion exchange [ 23 , 24 ]. To that end, it remained to be determined what dosage of Ag + is acceptable for plant irrigation water under ISS-like environmental conditions (~3000 ppm carbon dioxide) and whether Ag + will need to be removed from potable water before use as space crop irrigation water.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this is due to the high cation-exchange capacity of arcillite that allows for the adsorption of positively charged ions due to negatively charged surfaces. We expected that arcillite as a substrate with high cation-exchange capacity would act like biochar, which holds a lower cation-exchange capacity, in its ability to diminish the uptake of toxic metals in plants by immobilizing the metal across the surface of the substrate via ion exchange [ 23 , 24 ]. To that end, it remained to be determined what dosage of Ag + is acceptable for plant irrigation water under ISS-like environmental conditions (~3000 ppm carbon dioxide) and whether Ag + will need to be removed from potable water before use as space crop irrigation water.…”
Section: Introductionmentioning
confidence: 99%
“…Some phytochemicals have an antioxidative action, for example, carotenoids, flavonoids, and other phenolics [13]. Previous studies have shown that spinach grown in soil treated with organic amendments showed higher leaf quality due to an increase in nutrients, antioxidant enzymes, photosynthetic pigments, and bioactive compounds (polyphenols, flavonoids, and carotenoids) [14][15][16][17]; this is due to the changes that organic amendments cause in the properties and structure of the soil [17].…”
Section: Introductionmentioning
confidence: 99%